2017
DOI: 10.1155/2017/7356362
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising the Factors Affecting Retention in Care of Patients on Antiretroviral Treatment in Kabwe District, Zambia, Using the Ecological Framework

Abstract: Background. HIV remains a major public health challenge in Zambia. The roll-out of antiretroviral treatment (ART) has engendered new challenges in retention in care. Objective. To conceptualise the factors affecting retention in care of ART patients at three primary healthcare facilities using the ecological framework. Method. Qualitative data were collected through in-depth interviews with 45 ART patients and three focus group discussions with 20 healthcare providers from three primary healthcare facilities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 27 publications
8
58
0
Order By: Relevance
“…This often led to lapses in ART adherence. In recent qualitative and quantitative studies conducted among countries in sub-Saharan Africa, hunger and household food insecurity were identified as major barriers to ART adherence [20,21,23,[46][47][48]. Several studies in the region have reported similar findings, and in some cases, individuals stopping treatment completely due to anxiety over side effects from ART medication when access to food was compromised and inadequate [18,19,27].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This often led to lapses in ART adherence. In recent qualitative and quantitative studies conducted among countries in sub-Saharan Africa, hunger and household food insecurity were identified as major barriers to ART adherence [20,21,23,[46][47][48]. Several studies in the region have reported similar findings, and in some cases, individuals stopping treatment completely due to anxiety over side effects from ART medication when access to food was compromised and inadequate [18,19,27].…”
Section: Discussionmentioning
confidence: 90%
“…Empirical studies across settings in sub-Saharan Africa indicate that ART adherence can be influenced by risk factors operating at multiple levels. At the individual level, ART adherence is associated with age, gender, educational level, forgetfulness, ART duration, alcohol use, stress, lack of money, and lack of disclosure status [17][18][19][20][21]. At the household level, ART adherence is associated with household food insecurity, household socioeconomic status, lack of family support, and use of traditional medicine [18,20,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is might be due to long travel distance to health facility because large proportion of participants in the current study were from rural residence. Previous studies also showed that long travel distance and lack of money for traveling to health institution affect ART adherence and follow-up visit within the recommended time [17,18]. Besides, the median time to complete the enhanced adherence counseling session was greater than 24 weeks in men, which is very far away from the suggested time [3,10,12].…”
Section: Discussionmentioning
confidence: 98%
“…[24][25][26] This is seemingly true for this study which found a significantly higher median CD4 value in patients enrolled under the T&T. Lower retention has been reported in patients with higher CD4 count and gaining weight in Nigeria and South Africa. 27,28 In the same light, "feeling healthy'' was reported as a barrier to ART initiation and engagement by a study in Cameroon and another in Mozambique. 23,29 These suggest that proper counselling, therapeutic education and close follow up amongst healthier patients initiating ART maybe be helpful in improving ART retention, especially under the T&T context.…”
Section: Discussionmentioning
confidence: 93%